What Are the Risk Factors for Dislocation of Hip Bipolar Hemiarthroplasty Through the Anterolateral Approach? A Nested Case‐control Study. Issue 12 (December 2016) - Li, Lianhua; Ren, Jixin; Liu, Jia; Wang, Hao; Sang, Qinghua; Liu, Zhi; Sun, Tiansheng
Abstract: Background: Hip dislocation after treatment of a femoral neck fracture with a hemiarthroplasty remains an important problem in the treatment of hip fractures, but the associations between patient factors and surgical factors, and how these factors contribute to dislocation in patients who have undergone bipolar hemiarthroplasty through an anterolateral approach for femoral neck fracture currently are only poorly characterized. Questions/purposes: We evaluated patients with bipolar hemiarthroplasty dislocation after surgery for femoral neck fracture treated through an anterolateral approach and asked: (1) What are the frequency, characteristics, and risk factors of bipolar hemiarthroplasty dislocations? (2) What are the frequency, characteristics, and risk factors of bipolar hemiarthroplasty dissociations? Methods: A review of hospital records for patients who underwent bipolar hip hemiarthroplasty for femoral neck fracture at one hospital between July 2004 and August 2014 was conducted. During that time, 1428 patients were admitted with a diagnosis of femoral neck fracture; 508 of these patients underwent bipolar hip hemiarthroplasty, of whom 61 died and 23 were lost to followup during the first year, leaving 424 (83%) available for analysis. The remainder of the patients during that time were treated with internal fixation (512), unipoloar hip arthroplasty (17), or THA (391). For each patient with dislocation, we selected five control patients from the cohort according to sex, age (± 3 years), and year of entry in the study to eliminate some confounding factors. We recorded patient characteristics regarding demographics, medical comorbidities, Katz score, American Society of Anesthesiologists score, Mini‐Mental State Examination (MMSE) score, and anesthesia type. Medical comorbidities included diabetes, chronic pulmonary disease, heart disease, neuromuscular diseases, and dementia. Univariate analyses were used to search for possible risk factors. Conditional logistic regression analyses on dislocation or dissociation were performed to estimate hazard rates (HRs) and corresponding 95% CIs with covariates of a probability less than 0.1 in univariate analysis. Results: In this cohort, there were 26 dislocations including four that were also dissociations. The proportion of patients experiencing a dislocation was 6% (26 of 424). The mean interval from surgery to dislocation was 56 weeks (range, 0‐433 weeks), and 18 dislocations (69%) occurred within 3 months after surgery. Three variables were independently associated with an increased risk of hip dislocation: dementia (HR, 3.51; 95% CI, 1.19‐10.38; p = 0.02), discrepancy of offset (HR, 1.72; 95% CI, 1.15‐2.58; p = 0.008), and lower MMSE score (HR, 0.93; 95% CI, 0.88‐0.98; p = 0.007). The proportion of patients experiencing a dissociation was 0.9% (four of 424). The result of conditional logistic regression for dissociation showed that cup size smaller than 43 mm was the risk factor (HR = 513.05). However, there was no statistical difference with the probability equaling 0.47. Conclusions: After the anterolateral approach for treatment of femoral neck fracture using bipolar hemiarthroplasty, 6% of hips dislocated and 0.9% experienced dissociation. Cognitive dysfunction and discrepancy of offset were independent risk factors associated with an increased risk of prosthetic dislocation. The small cup without a safety ring may be the risk factor of dissociation. Discrepancy of offset should be avoided during the operation by performing an accurate femoral osteotomy and choosing an adequate femoral stem neck length. For patients with cognitive dysfunction and a small cup, suturing the joint capsule during the operation and reinforcing protective measures after surgery might reduce the occurrence of dislocation and dissociation, however a study addressing this is necessary to confirm this. Level of Evidence: Level III, therapeutic study.